The crystal structure and Raman spectrum of the sodium salt of 5-Acetic acid hydantoin - Nogueira, B.A.; Tabanez, A.M.; Henriques, M.S.C.; Paixão, J.A.; ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2020)
The sodium salt of 5-acetic acid hydantoin (5AAH) was synthesized, and its crystal structure determined by single crystal X-ray diffraction. The material was found to exhibit rather unusual structural features. Firstly, contrarily to what is most common for hydantoins, the 5AAH molecules in the crystal bind the sodium ions through coordination via its oxygen atoms (instead of via a deprotonated ring nitrogen). In second place, the molecular formula of the salt is Na(5AAH)2, i.e., the formal charge of the hydantoin in the crystal is −0.5 e. Finally, the conformation adopted by the 5AAH molecules in the crystal of the salt is neither the most stable conformer for the isolated molecule (and observed before in the gas phase of the compound), nor that present in the neat crystalline compound (most stable polymorph at room temperature). These results show that 5AAH is a structurally very versatile molecule, which is able to participate in strong intermolecular interactions that can supersede the intrinsic higher structural stability of the individual molecules and lead to selection of different higher energy conformers on formation of a crystalline phase. The Raman spectrum of the newly synthesized salt was also obtained and used to extract further structural details of the crystal, in particular on the prevalent intermolecular interactions. The results (both structural and spectroscopic) obtained for the studied sodium salt of 5AAH are also compared with those relative to the neat 5AAH most stable crystalline polymorph at room temperature. To help the interpretation of the spectra, DFT(B3LYP)/6–311++G(d,p) calculations were undertaken on simple models based on the structural elements of the crystals. © 2020
Keywords: 5-acetic acid hydantoin sodium salt; DFT Calculations; Raman Spectroscopy; Single Crystal x-ray Diffraction